THE LAW ENFORCEMENT AGAINST NARCOTICS CRIMINAL ACTIONS WHO SHOULD BE ON REHABILITATION - Bambang Tri Bawono; Gunarto Gunarto (UNISSULA, 2022)
The purpose of this study was to determine and analyze the process of law enforcement for narcotics crimes and the legal basis used as a reference for rehabilitation. The approach method used in this research is a sociological juridical approach. Criminal sanctions related to the five criminal acts above also have different consequences, depending on the type of narcotic class used. Criminal provisions regarding narcotics criminals possessing, storing, controlling or providing narcotics are regulated in Article 112, Article 117, and Article 122 of Act No. 35 of 2009 concerning Narcotics. In addition to the law prohibiting possessing, storing, controlling or providing narcotics, the Narcotics Law also explicitly regulates the prohibition of producing, importing, exporting, or distributing narcotics. The prohibition is regulated in Article 113, Article 118, and Article 123 of Act No. 35 of 2009 concerning Narcotics. The results of this study indicate that the process of law enforcement against narcotics crimes is carried out through investigation, prosecution, and examination in court. While the legal basis used by judges to rehabilitate narcotics criminals is: Supreme Court Circular No. 4 of 2010 concerning Placement of Victims of Abuse and Narcotics Addicts in Medical Rehabilitation and Social Rehabilitation Institutions.